2013
DOI: 10.1213/ane.0b013e3182a8fa97
|View full text |Cite
|
Sign up to set email alerts
|

Under General Anesthesia Arginine Vasopressin Prevents Hypotension but Impairs Cerebral Oxygenation During Arthroscopic Shoulder Surgery in the Beach Chair Position

Abstract: A prophylactic bolus administration of AVP prevents hypotension associated with BCP in patients undergoing shoulder surgery under general anesthesia. However, it was associated with regional cerebral but not jugular venous oxygen desaturation on upright positioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
47
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 37 publications
6
47
0
Order By: Relevance
“…Some data suggest that this drug and other vasoconstrictors may reduce rScO 2 measured with NIRS. 51,52 Since scalp blood flow is not autoregulated and because COx measures the relationship between low-frequency changes in rScO 2 and blood pressure, the effects of phenylephrine on NIRS measurements, if any, seem minimal.…”
Section: Discussionmentioning
confidence: 99%
“…Some data suggest that this drug and other vasoconstrictors may reduce rScO 2 measured with NIRS. 51,52 Since scalp blood flow is not autoregulated and because COx measures the relationship between low-frequency changes in rScO 2 and blood pressure, the effects of phenylephrine on NIRS measurements, if any, seem minimal.…”
Section: Discussionmentioning
confidence: 99%
“…Third, phenylephrine yields higher cerebral perfusion pressure in patients with traumatic brain injury compared with dopamine and norepinephrine, suggesting the desirable property of this vasoconstrictor agent in the cerebral circulation [22]. It is crucial to note that another vasoconstrictor agent vasopressin reduces cerebral oxygenation during the beach chair position despite the mean blood pressure elevation [4]. These results suggest that phenylephrine is probably one of the most valuable vasopressors, which are available in the clinical practice, to preserve cerebral oxygenation during anesthesia in the beach chair position.…”
Section: Discussionmentioning
confidence: 99%
“…However, a possible decrease in cerebral oxygenation related to this position has been suggested by many previous reports, although exact mechanisms of the catastrophic complication remain to be determined [2][3][4].…”
Section: Introductionmentioning
confidence: 86%
“…It has been stated that mean arterial blood pressure (MAP) should be targeted within 15-20% of baseline during upright positioning [23]. However, some studies observed cerebral desaturation despite maintaining blood pressure with phenylephrine [24] or vasopressin [25]. The effect of general anesthesia was compared with regional anesthesia and sedation (awake group) during BCP [26].…”
Section: Key Pointsmentioning
confidence: 99%